ANALISIS LATIHAN MENULIS BUKU ICH LIEBE DEUTSCH 3 UNTUK SISWA SMA/MA KELAS XII SEMESTERÂ GANJIL - FATIMAH A, LADIKA (LATERNE, 2018)
The exercise book Ich Liebe Deutsch 3  is a new teaching material for Seniors High School. Therefore, it is important to analyze the suitability between the exercise materials of the book and the competency of the curiculum (curiculum 2013). This research has a goal that would like to know the suitability of writing skill exercises in book Ich Liebe Deutsch 3 with curriculum 2013. The problem of research is: How is the the suitability of writing skill exercises in book Ich Liebe Deutsch 3 with curriculum 2013 for the SMA / MA class XI Isemester 1?. The method  of this research is descriptive qualitative. The theory of the research are curriculum 2013 and the level of the writing test of Nurgiyantoro. The data are from the practice book Ich Liebe Deutsch 3  by Dyah Sapta Wulandari. There are 13 writing skills exercises in Lesson 4, which has  analyzed with the competency of the valid curiculum (curiculum 2013). The results of the research are: There are 7 writing skills exercises that fit with curriculum 2013 and there are 6 writing skills exercises that not fit with curriculum 2013. Hopefully, the writers of the book would make a correction. Keywords: writing skill, exercises, Ich Liebe Deutsch 3